A theoretical model of design fixation. Issue 3 (2nd October 2017) - Nguyen, Thanh An; Zeng, Yong
Abstract: Design fixation describes a phenomenon in which designers fail to solve a design problem due to their strong mental attachment to an internal or external inspiring source. A number of empirical research studies aimed at identifying the causes behind design fixation and developing approaches for overcoming it. In this paper, we propose a theoretical model of design fixation in which the concepts of perceived fitness and expected fitness are introduced. Interpretation of existing findings on fixation and hypotheses are derived to show the applications of the model. In addition, a method of evaluation of design fixation is introduced and demonstrated with an example.